Experimental–computational study towards heat generation in thick laminates under fatigue loading. (November 2015) - Lahuerta, F.; Nijssen, R.P.L.; van der Meer, F.P.; Sluys, L.J.
Highlights: A method to forecast the temperature raise due to fatigue is described for composite materials. When temperatures achieve glass transition temperatures, a decrease in fatigue performance was observed. The methodology was confirmed to be accurate in comparison with the experimental observations. The method links the hysteresis area loss factor and the internal volumetric heat that cause the material heating. Abstract: Due to the poor thermal conductivity of composites and the material heating that occurs during fatigue loading, high temperatures may appear in the laminate. Since the mechanical properties of composites are dependent on temperature, the fatigue performance may be affected negatively. This effect will occur when local temperatures approach the glass transition temperature of the matrix. The aim of this work is to study heating in fatigue experiments on thick laminates. For this purpose fatigue tests on 10, 20 and 30 mm thick coupons under different loading conditions are reported. A reduction in fatigue life due to internal heating is shown. A finite element model to predict the heating of thick laminates during dynamic loading is described and evaluated with experimental data.